Potassium Intake Prevents the Induction of the Renin-Angiotensin System and Increases Medullary ACE2 and COX-2 in the Kidneys of Angiotensin II-Dependent Hypertensive Rats - Gonzalez, Alexis A.; Gallardo, Matias; Cespedes, Carlos; Vio, Carlos P. (Frontiers in Pharmacology, 2019)
In angiotensin II (Ang II)-dependent hypertension there is an increased expression of proximal tubule angiotensinogen (AGT), collecting duct renin and angiotensin converting enzyme (ACE), which contributes to intratubular Ang II formation. Ang II acts on Ang II type 1 receptors promoting sodium retention and vasoconstriction. On the other hand, ACE2-Ang-(1-7) axis and medullary prostaglandins counteract the effects of Ang II, promoting natriuresis and vasodilation. Human studies as well as animal models demonstrate that dietary potassium (K+) intake lowers blood pressure. In this report we evaluate the expression of AGT, ACE, medullary prorenin/renin (not juxtaglomerular), ACE2 and cyclooxygenase-2 (COX-2) in Ang II-infused rats fed with high K+ diet (2%) during 14 days. Dietary K+ enhances diuresis when compared to control rats and increased diuresis in Ang II-infused rats. The rise in systolic blood pressure in Ang II-infused rats was attenuated in Ang II + K+ group. Ang II-infused rats showed increased renal protein levels of AGT, ACE and medullary prorenin/renin. This effect was attenuated in Ang II + K+ group. Ang II infusion decreased ACE2 compared to control group; however, K+ diet prevented this effect. Furthermore, medullary COX-2 was dramatically induced in K+ diet and Ang II + K+ group. These results indicate that a high K+ diet attenuates Ang II-dependent hypertension by preventing the induction of ACE, AGT and collecting duct renin and the enhancement of medullary COX-2 and ACE2 protein expression in the kidney.